The Renewed Christocentric Synthesis in Joseph Ratzinger’s Logos-centric Symphony - Roland Millare (Wrocławski Przegląd Teologiczny)
This article aims to present Joseph Razinger’s Christocentric approach to the question of the relation between faith and reason. Modernity introduces the separation between faith and reason, which results in the limitation of reason and the subordination of logos to ethos. This disunity, however, between faith and reason and the primacy of the ethos over logos affects the nature and mission of theology. In contrast to the loss of the integrative harmony between faith and reason, Joseph Ratzinger argues for the distinction and unity between faith and reason built upon the primacy of logos and a Christocentric approach. The author also intends to prove that although Ratzinger describes his theology as “fragmentary” and “incomplete,” he has gifted the Church with a renewed theological symphony that flourishes only in conjunction with the gift of faith working in concert with reason. In Ratzinger’s view only faith can enable reason to overcome the self-imposed limitation developed by modern thinkers such as Immanuel Kant. Finally, the article will demonstrate that the crowning achievement of Joseph Ratzinger/Benedict XVI’s theology is the recognition of the primacy of love as embodied by the saints who are witnesses of the transformative power of knowing and loving Jesus, the Incarnate Logos.